A identidade da mão e as anatomias do nu no desenho e no desenhar de João Cutileiro - Rahim, Shakil Yussuf, 1979- (2016)
The Cutileiro’s female nude drawing is an erotization sociology through the functions of a variable gaze phenomenology. The draughtsperson hand identifies the gesture of the body and captures it in the transformation of instant and urgency. In this intentional framework, the paper analyses the operating graphical interfaces through three pairs of factors involved in to draw. The “theme and figure” explores the identities of the body and the gender. The “technic and graphics” studies the outline geometry and trace variability. The “volume and pose” deals with the position, motion and gravity on deviations of human proportion